2011
DOI: 10.1080/10413200.2010.534544
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulation of Practice Behavior Among Elite Youth Soccer Players: An Exploratory Observation Study

Abstract: This study aimed to measure behavioral correlates of self-regulation in elite youth soccer players. Behaviors regarded as indicative of self-regulated learning were identified by interviewing six expert youth soccer coaches. These behaviors were observed during practice of eight elite youth soccer players aged 15-17 years, and linked with self-reported self-regulated learning scores to describe behavioral correlates of self-regulation. Results indicated that self-regulated learning is reflected in taking respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 34 publications
(37 reference statements)
3
39
1
Order By: Relevance
“…These behavioral examples were also found in items mentioned by the expert badminton coaches, for instance, "pay attention when coach is giving them feedback", "eagerness in following the practices", and "arrived early for practice". Item "start practicing on their own before the practice starts" mentioned in this study was similar to item in the previous study on soccer players in Dutch done by Toering et al (2011) about "works on improvement of his weak points during the 30 minutes before start of practice session". Several other items such as "verbally approaches coach during instruction", "verbally approaches coach during exercise", and "verbally approaches coach after exercise" were also replicated in one behavioral item "actively ask questions/advice after/during practice" within this study.…”
Section: Coach Interviewsupporting
confidence: 54%
See 2 more Smart Citations
“…These behavioral examples were also found in items mentioned by the expert badminton coaches, for instance, "pay attention when coach is giving them feedback", "eagerness in following the practices", and "arrived early for practice". Item "start practicing on their own before the practice starts" mentioned in this study was similar to item in the previous study on soccer players in Dutch done by Toering et al (2011) about "works on improvement of his weak points during the 30 minutes before start of practice session". Several other items such as "verbally approaches coach during instruction", "verbally approaches coach during exercise", and "verbally approaches coach after exercise" were also replicated in one behavioral item "actively ask questions/advice after/during practice" within this study.…”
Section: Coach Interviewsupporting
confidence: 54%
“…Ertmer and Newby (1996) proposed a model for a metacognitive component of self-regulation which covers: (a) planning how to improve before taking action; (b) self-monitoring actions related to the personal goal; (c) evaluating process and outcome after execution; and (d) reflecting back on the whole process. Furthermore, Toering et al (2011) suggested that the motivational variable of self-regulated learners is indicated in the motivational belief (e.g. self-efficacy) and motivational outcome (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, he should monitor and evaluate the process, should put effort in it and believes that he is able to achieve his goal (self-efficacy) (Ertmer & Newby, 1996;Zimmerman, 1986Zimmerman, , 2006. This self-regulated learning can for example be expressed by players by being on time at training, taking initiative during exercises, and asking for feedback from the trainer (Elferink-Gemser et al, 2013;Toering et al, 2011). Research has shown that higher skilled athletes have better selfregulatory skills, especially reflection (Cleary & Zimmerman, 2001;Jonker, Elferink-Gemser, de Roos, & Visscher, 2012;Toering, Elferink-Gemser, Jordet, & Visscher, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Athletes with a high level of reflection are expected to improve themselves on those skills which are important for their position. Consequently, they are hypothesized as more often attaining the elite level of performance compared to players with lower reflection scores (Jonker, Elferink-Gemser, Toering, Lyons, & Visscher, 2010;Toering et al, 2011). This study first investigated the importance of ball control and (self-reported) self-regulatory skills for talented basketball players in order to achieve the elite level of performance in adulthood (>20 years).…”
Section: Introductionmentioning
confidence: 99%